PERGESERAN MAKNA DAN PEMBERDAYAAN WAKAF (ZISWAF: Jurnal Zakat dan Wakaf, 2016)
Endowments to save a great potential to be developed into a productive asset, which in the end was not only able to support socio-religious services, but also directed to support the various initiatives and social justice objectives. In addition, of course, the waqf is the economic potential of extraordinary magnitude. The fact that support is today Indonesia is the largest country to 4 and the largest Muslim population in the world, the majority of Muslims is rich with natural resources and endowments part of Islamic teachings potential for empowerment of Muslims, the nation and the State. In fact, when it has passed Law No. 41 of 2004 on Waqf and Government Regulation No. 42 of 2006 on the implementation of Law No. 41 of 2004, and has issued Fatwa Indonesian Ulema Council (MUI) on the permissibility of cash waqf in May 2002 as evidence in support of the government, parliament, the clergy and the people of Indonesia on the importance of empowering asset endowments as a strategic step development of the people, nation and state of Indonesia.